Investigation of the miRNA146a and miRNA155 gene expression levels in patients with multiple sclerosis. (August 2020) - Shademan, Behrouz; Nourazarian, Alireza; Nikanfar, Masoud; Biray Avci, Cigir; Hasanpour, Mehdi; Isazadeh, Alireza
Highlights: MicroRNA-146a and microRNA-155 considered as the inflammatory microRNAs. MicroRNA-146a and microRNA-155 level was increased in patients with MS compared to controls. Increased expression levels of MicroRNA-146a and MicroRNA-155 may be associated with the pathogenesis of MS disease. Abstract: Multiple sclerosis (MS) is a chronic inflammatory disease and the most common neurodegenerative status. MicroRNAs play an important role in macrophage response to inflammatory processes, and alterations in miRNA levels trigger the inactivation of specific T lymphocytes. As a result, these factors can lead to autoimmune diseases such as MS. Therefore, to determine the role of MicroRNA-146a and MicroRNA-155 in MS patients, their expression levels in serum of MS patients were compared with healthy controls. In this study, the expression levels of MicroRNA-146a and MicroRNA-155 in 30 serum samples of MS and healthy patients as a control group. MicroRNA extraction and cDNA synthesis was performed according manufacture protocols. The expression levels of MicroRNAs were evaluated by Real Time-PCR. MicroRNA-146a and MicroRNA-155 levels were increased in patients with MS compared to controls. The results demonstrated that EDSS score are increased with increasing level of MicroRNA-146a and MicroRNA-155. ROC curve analysis showed that the area under curve (AUC) was significant for MicroRNA-146a and MicroRNA-155. Increased expression levels of MicroRNA-146a and MicroRNA-155 may be associated with the pathogenesis of MS disease. If this study is conducted in a larger sample population and the above results can be used to identify patients or control patients who are under medical care.